Highly efficient generation of single-mode photon pairs from a crystalline whispering-gallery-mode resonator source - Foertsch, Michael; Schunk, Gerhard; Fuerst, Josef U.; Strekalov, Dmitry; Gerrits, Thomas; Stevens, Martin J.; Sedlmeir, Florian; Schwefel, Harald G. L.; Nam, Sae Woo; Leuchs, Gerd; Marquardt, Christoph (Physical Review A - Atomic, Molecular, and Optical Physics, 2015)
We report a highly efficient source of narrow-band photon pairs based on parametric down-conversion in a crystalline whispering-gallery-mode resonator. Remarkably, each photon of a pair is detected in a single spatial and temporal mode, as witnessed by Glauber's autocorrelation function. We explore the phase-matching conditions in spherical geometries, and determine the requirements for single-mode operation. Understanding these conditions has allowed us to experimentally demonstrate a single-mode pair-detection efficiency of 1.13×106 pairs/s per mW pump power per 26.8 MHz bandwidth.
CRIS-Team Scopus Importer:2022-06-05